Helix Nucleation by the Smallest Known α‐Helix in Water. Issue 29 (25th May 2016) - Hoang, Huy N.; Driver, Russell W.; Beyer, Renée L.; Hill, Timothy A.; D. de Araujo, Aline; Plisson, Fabien; Harrison, Rosemary S.; Goedecke, Lena; Shepherd, Nicholas E.; Fairlie, David P.
Abstract: Cyclic pentapeptides (e.g. Ac‐(cyclo‐1, 5)‐[KAXAD]‐NH2 ; X=Ala, 1 ; Arg, 2 ) in water adopt one α‐helical turn defined by three hydrogen bonds. NMR structure analysis reveals a slight distortion from α‐helicity at the C‐terminal aspartate caused by torsional restraints imposed by the K( i )–D( i +4) lactam bridge. To investigate this effect on helix nucleation, the more water‐soluble 2 was appended to N‐, C‐, or both termini of a palindromic peptide ARAARAARA (≤5 % helicity), resulting in 67, 92, or 100 % relative α‐helicity, as calculated from CD spectra. From the C‐terminus of peptides, 2 can nucleate at least six α‐helical turns. From the N‐terminus, imperfect alignment of the Asp5 backbone amide in 2 reduces helix nucleation, but is corrected by a second unit of 2 separated by 0–9 residues from the first. These cyclic peptides are extremely versatile helix nucleators that can be placed anywhere in 5–25 residue peptides, which correspond to most helix lengths in protein–protein interactions. Abstract : Pep up your peptide : When an α‐helical cyclic pentapeptide 1 was appended to one or both ends of a palindromic peptide ARAARAARA (≤5 % helicity), 67, 92, or 100 % α‐helicity of the resulting peptide was observed (see picture). From the C‐terminus of peptides, 1 nucleated at least six α‐helical turns. Imperfect alignment of a backbone amide in 1 reduced helix nucleation when 1 was attached to the N‐terminus, but was corrected by a second unit of 1 .